Tunable Optical and Photoluminescence Properties of Metal X (Ni, Co, Mn, Ag)-Doped ZnSe Quantum Dots: Structural, Spectroscopic, and Colorimetric Analysis - Bui, Thi Diem; Nguyen, Quang Liem; Nguyen, Van Cuong; Nguyen, Trong Tang; Dang, Huu Phuc (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
This study explores the impact of Ni, Co, Mn, and Ag doping on the optical and photoluminescence properties of ZnSe quantum dots (QDs). Structural analysis confirms successful dopant incorporation, with XRD revealing lattice strain-induced shifts. Optical studies show that Ni²⁺ and Co²⁺ induce blue shifts, while Mn²⁺ and Ag⁺ create redshifted emissions. Photoluminescence analysis demonstrates that Mn²⁺ doping enhances quantum efficiency to 49.52% via the 4T1 → 6A1 transition. Ag+-doped ZnSe exhibits blue-shifted emissions but suffers from defect-related non-radiative losses. CIE color coordinates validate tunable emissions, confirming potential applications in LEDs, displays, and bioimaging. These findings provide insights into dopant-induced band structure modifications, advancing the design of high-performance luminescent materials for optoelectronics. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).